Thinking being : introduction to metaphysics in the classical tradition - Perl, Eric David. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2014)
In Thinking Being , Eric Perl articulates central ideas and arguments regarding the nature of reality in Parmenides, Plato, Aristotle, Plotinus, and Aquinas. He shows that, throughout this tradition, these ideas proceed from and return to the indissoluble togetherness of thought and being, first clearly expressed by Parmenides. The emphasis throughout is on continuity rather than opposition: Aristotle appears as a follower of Plato in identifying being as intelligible form, and Aquinas as a follower of Plotinus in locating the first principle "beyond being". Hence Neoplatonism, itself a coherent development of Platonic thought, comes to be seen as the mainstream of classical philosophy. Perl's book thus contributes to a revisionist understanding of the fundamental outlines of the western tradition in metaphysics.